Bilingualism and Vocabulary Learning: A Comparison between Baluchi and Persian EFL Learners - Yahya Keikhaie; Amirali Khoshkhoonejad (Intelektual Pustaka Media Utama, 2015)
Bilingualism can be broadly defined as the ability to speak 2 languages; however there are many grey areas when establishing which are the first language, second language and third language of a bilingual. The paper reports on a study exploring the effect of bilingualism on the learning of a vocabulary learning of two groups of Iranian male students: Baluchi bilinguals and Persian monolingual. The present study is based on data from 80 monolingual Persian-speaking learners of English and 80 bilingual Baluchi-Persian-speaking learners of English. All the participants were male studying English as a foreign language at pre-university of Sistan and Baluchestan in Iran. The results indicates that Baluchi-Persian bilingual speakers outperformed in general and in L3 recognition vocabulary learning. The findings of this paper also showed that no significant difference was seen between Persian-speaking learners and Baluchi-Persian-speaking in L3 production vocabulary learning.